APLIKASI PELAPORAN DATA OPERASIONAL SUMUR-SUMUR MINYAK DAN GAS DI PETROGAS ISLAND LIMITED SALAWATI BERBASIS WEB - Iriene Surya Rajagukguk; Velly Bernard Latul (LPPM Poltek ST Paul, 2020)
The purpose of conducting this research is to help employees, especially in the production maintenance division in clerck in reporting the logging of Wells – Oil and Gas Wells, so as to also help minimize the excessive use of paper. The system uses XAMPP, PHP, and MySQL software. Xampp is used as a web server software, PHP is used as a server-side script programming language designed for web development, while MySQL is used as database creation software. The result of this study is the Well Reporting Logging Application – Oil and Gas Wells which greatly assists the clerk admin's work in managing Oil and Gas Well data, and yamg data is managed by admin clerks more regularly and can also minimize excessive use paper. Younger leaders in obtaining and viewing data information – well and gas data.